Robust and orange-yellow-emitting Sr-rich polytypoid α-SiAlON (Sr3Si24Al6N40:Eu2+) phosphor for white LEDs - Mehdi Estili; Rong-Jun Xie; Kohsei Takahashi; Shiro Funahashi; Tohru S. Suzuki; Naoto Hirosaki (Science and Technology of Advanced Materials)
Nitrides and oxynitrides isostructural to α-Si3N4 (M-α-SiAlON, M = Sr, Ca, Li) possess superb thermally stable photoluminescence (PL) properties, making them reliable phosphors for high-power solid-state lighting. However, the synthesis of phase-pure Sr-α-SiAlON still remains a great challenge and has only been reported for Sr below 1.35 at.% as the large size of Sr2+ ions tends to destabilize the α-SiAlON structure. Here, we succeeded to synthesize the single-phase powders of a unique ‘Sr-rich’ polytypoid α-SiAlON (Sr3Si24Al6N40:Eu2+) phosphor with three distinctive Sr/Eu luminescence sites using a solid-state remixing-reannealing process. The Sr content of this polytypoid structure exceeds those of a few previously reported structures by over 200%. The phase purity, composition, structure, and PL properties of this phosphor were investigated. A single phase can be obtained by firing the stoichiometric mixtures of all-nitride precursors at 2050°C under a 0.92 MPa N2 atmosphere. The Sr3Si24Al6N40:Eu2+ shows an intense orange-yellow emission, with the emission maximum of 590 nm and internal/external quantum efficiency of 66%/52% under 400 nm excitation. It also has a quite small thermal quenching, maintaining 93% emission intensity at 150°C. In comparison to Ca-α-SiAlON:Eu2+, this Sr counterpart shows superior quantum efficiency and thermal stability, enabling it to be an interesting orange-yellow down-conversion luminescent material for white LEDs. The experimental confirmation of the existence of such ‘Sr-rich’ SiAlON systems, in a single-phase powder form, paves the way for the design and synthesis of novel ‘Sr-rich’ SiAlON-based phosphor powders with unparalleled properties.